Risks and outcome of fungal infection in neutropenic children with hematologic diseases - Aytaç, Selin; Yildirim, Inci; Ceyhan, Mehmet; Cetin, Mualla; Tuncer, Murat; Kara, Ateş; Cengiz, A Bülent; Seçmeer, Gülten; Yetgin, Sevgi (The Turkish Journal of Pediatrics, 2010)
In this retrospective study, we report the results of antifungal treatments (AFTs) in febrile neutropenic episodes in patients with acute lymphoblastic leukemia (ALL), acute myeloid leukemia (AML) and aplastic anemia (AA) in our center. From January 2004 to December 2005, a total of 52 patients and 221 febrile neutropenic episodes were evaluated. AFT was started in 96 (43%) of the 221 episodes. Amphotericin B and fluconazole were used in 44 (46%) and 52 (54%) febrile neutropenic episodes, respectively. Microbiologically or histopathologically evident fungal infections were detected in 35 of 96 febrile neutropenic episodes. The mortality rate due to fungal infection was higher in patients with AA (7/8 patients) and AML (7/12 patients) than in ALL patients (1/32). Mortality for the whole group was 28%. When the mortality rate was compared between the two treatment groups (amphotericin B vs fluconazole), mortality was significantly higher in patients receiving amphotericin B [n = 14 (93%) and n = 1 (7%), respectively].